Achieving Supply Chain Performance During the Covid-19 Pandemic: Antecedent Studies and the Important Role of Supply Chain Agility - Sujatmika Sujatmika; Katon Pratondo; Anggraeni Pratam Indrianto; Titik Kusmantini; Aufi Rahmanti Pohan (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
The COVID-19 pandemic seriously threatens the sustainability of a business by affecting its supply chain. To address business continuity in the future, companies need to develop their strategies through supply chain agility. Supply chain agility is largely determined by three influencing factors, namely strategic resources, learning orientation, and technology orientation. This study has involved 120 SMEs (Small Medium Enterprises) in Yogyakarta. The data has been processed using PLS-SEM. The results of this study found that strategic resources have a positive effect on supply chain agility, learning orientation has a positive effect on supply chain agility, technology orientation has a positive effect on supply chain agility, and supply chain agility has a positive effect on business performance.